Pengaruh Penggunaan Tabung Induksi Terhadap Konsumsi Bahan Bakar Sepeda Motor Bensin 4 Langkah - Junaidi Supratman; Herry Wardono; M.Dyan Susila (Jurnal Ilmiah Teknik Mesin, 2013)
YEIS tube (Yamaha Energy Induction System) has been able to enhance the performance of the motorcycle. Therefore, the use of induction tube on a 4-stroke motorcycle is expected to be able to increase the volumetric efficiency of the suction stroke, so that the power (acceleration) of the engine can increase at low speed. Tests of using induction tubein a 4-stroke motorcycle is required to observe the effect of the induction tube position on its performance and emission.the engine performance tests were carried out in road tests at an average speed of 40 kph. It was conducted before and after using the induction tube, and the induction tube mountings on intake manifold were varied at positions of JS150 (15 mm from intake manifold), JS 375 (37,5 mm), and JS600 (600 mm). Each type of test was performed 3 times to get it’s average.From the results, it was found that the fuel consumption of the motorcycle could maximally reduce by 27.8% in mounting JS150 and the lowest engine consumption by 0.98% in mounting the intake manifold JS 600. The best result occurred in mounting of JS150 for all tests. JS150 is the optimal position. This due to JS150 is the closest position from intake manifold and the most farthest position from carburettor. Therefore, at mounting of JS150, residual air and fuel mixture can be fully drawn into both the line and tube of the induction tube. In contrast,JS600 is the farthest position from intake manifold, so that the residual air and fuel mixture cannot fully be drawn into the line and tube of the induction tube, the mixture is partially drawn into carburettor and induction tube, as in branched pipe system.Keywords : induction tube, petrol engine performance, YEIS.